Initiation of DNA replication in Bacillus subtilis: structural studies of the DnaA-DnaD interaction - Martin, Eleyna (2018)
Replication of genetic information is a vital process across all domains of life. Bacillus subtilis is considered the gram-positive model bacterium for studying DNA replication (Escherichia coli has been studied extensively as the gram-negative model) and is most representative of the ancestral phylum of prokaryotes. DNA replication has three distinct stages; initiation, elongation and termination. Replication initiation is the focus of this research and this process occurs at a single origin conserved throughout bacteria, termed oriC. B. subtilis primosomal machinery is formed of replication initiator proteins DnaA, DnaD and DnaB, the helicase loader DnaI, replicative helicase DnaC and primase DnaG. The role of the initiator proteins is to melt the DNA double helix and enable loading of the hexameric ring helicase onto each strand of DNA for bidirectional replication. Initiation is the first stage in DNA replication and despite its importance the molecular mechanisms of replication initiation remain largely unclear.